Bipolar disorders and suicide: stumbling twice with the same stone? - M. Sagué-Vilavella; G. Fico; G. Anmella; A. Giménez-Palomo; M. Gómez-Ramiro; M. Pons Cabrera; S. Madero; E. Vieta; A. Murru (European Psychiatry, 2022)
Introduction Suicide is the most terrible outcome of bipolar disorders (BD). It impacts families and healthcare professionals deeply. Family history of suicide (FHS) is one of its main risk factors, whereas lithium treatment and absence of substance use disorders (SUD) are two of its few modifiable protective factors.